Inovasi Sistem Stack Microbial Fuel Cell menggunakan Substrat Limbah Rumen Sapi serta Implementasinya sebagai Media Pembelajaran - Diya Novarina; Eko Swistoro; M. Lutfi Firdaus; Rosane Medriati (University of Bengkulu, 2018)
ABSTRACT[Innovation of microbial fuel cell stack system using cow rumen waste substrate and its implementation as a learning media]. The aims of this study are to: 1) describe the difference of Electric Motion (GGL), 2) describe the difference of electric power per unit area of the anode (Pa) which is produced between the series design MFC type series, parallel, mixed type 1 and mixed type 2, and 3) describe the significant difference of learning outcomes between the PBL learning model using MFC media with PBL learning model by using the electrical kit medium on dynamic electrical concept in SMA Muhammadiyah 4 Bengkulu. The free variable of this research are MFC stack system design (series, parallel, mixed types 1 and 2) and the dependent variable is GGL and electric power per unit of anode surface area. The results are obtained difference GGL and Pa between series design, parallel, mixed types 1 and 2 by comparison are 3: 1: 1,5: 2 whereas Pa ratio is 1: 10: 6: 2 with maximum GGL is obtained in series design of 3,29 V and Pa maximum in parallel circuit 21,76 mW / m2. Implementation of MFC series as a learning media used Problem Based Learning model on physics learning Implementation of MFC circuit with research design using one group pretest-posttest design. The testing of hypothesis with t-test shows tcount 2.739> ttable 2,001 and 95% significant level so it can be concluded there are significant differences in learning outcomes of PBL learning model by using MFC media with PBL learning model by using media Electric Kit on dynamic electrical concept in SMA Muhammadiyah 4 Bengkulu. Keywords: Stack Microbial Fuel Cell (MFC) Sistem; Rumen Cow Liquid Waste; Learning Media.